(untitled) (Journal of Scientific Research, 2013)
Let M be a G-ring. If M satisfies the condition (*) xaybz = xbyaz for all x, y, zÎM, a, bÎG, then we investigate commutativity of prime G-rings satisfying certain identities involving left centralizer. Keywords: Prime G-ring; Derivation; Generalized derivation; Left centralizer. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.14872 J. Sci. Res. 6 (1), 69-77 (2014)